Measuring the Impact of Distortions in Agricultural Trade in Partial and General Equilibrium - Tokarick, Stephen (Washington, D.C. : International Monetary Fund, 2003)
This paper provides quantitative estimates of the impact of removing agricultural support (both tariffs and subsidies) in partial- and general-equilibrium frameworks. The results show that agricultural support in industrial countries is highly distortionary and tariffs have a larger distortionary impact than subsidies. Removal of agricultural support would likely raise the international prices of food, resulting in an increase in the cost of food for many net-food- importing countries, although the increase is generally small. The results also show that most of the benefits from removing agricultural support accrue to the countries that liberalize.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet